Head-to-head comparison of plasma p-tau181, p-tau231 and glial fibrillary acidic protein in clinically unimpaired elderly with three levels of APOE4-related risk for Alzheimer's disease - Snellman Anniina; Ekblad Laura L.; Ashton Nicholas J.; Karikari Thomas K.; Lantero-Rodriguez Juan; Pietilä Elina; Koivumäki Mikko; Helin Semi; Karrasch Mira; Zetterberg Henrik; Blennow Kaj; Rinne Juha O. (Academic Press Inc., 2025)
Plasma phosphorylated tau (p-tau) and glial fibrillary acidic protein (GFAP) both reflect early changes in Alzheimer's disease (AD) pathology. Here, we compared the biomarker levels and their association with regional β-amyloid (Aβ) pathology and cognitive performance head-to-head in clinically unimpaired elderly (n = 88) at three levels of APOE4-related genetic risk for sporadic AD (APOE4/4 n = 19, APOE3/4 n = 32 or non-carriers n = 37). Concentrations of plasma p-tau181, p-tau231 and GFAP were measured using Single molecule array (Simoa), regional Aβ deposition with 11C-PiB positron emission tomography (PET), and cognitive performance with a preclinical composite. Significant differences in plasma p-tau181 and p-tau231, but not plasma GFAP concentrations were present between the APOE4 gene doses, explained solely by brain Aβ load. All plasma biomarkers correlated positively with Aβ PET in the total study population. This correlation was driven by APOE3/3 carriers for plasma p-tau markers and APOE4/4 carriers for plasma GFAP. Voxel-wise associations with amyloid-PET revealed different spatial patterns for plasma p-tau markers and plasma GFAP. Only higher plasma GFAP correlated with lower cognitive scores. Our observations suggest that plasma p-tau and plasma GFAP are both early AD markers reflecting different Aβ-related processes.